Reading Dye-Based Colorimetric Inks: Achieving Color Consistency Using Color QR Codes - Ismael Benito-Altamirano; Laura Engel; Ferran Crugeira; Miriam Marchena; Jürgen Wöllenstein; Joan Daniel Prades; Cristian Fàbrega (Chemosensors, 2024)
Color consistency when reading colorimetric sensors is a key factor for this technology. Here, we demonstrate how the usage of machine-readable patterns, like QR codes, can be used to solve the problem. We present our approach of using back-compatible color QR codes as colorimetric sensors, which are common QR codes that also embed a set of hundreds of color references as well as colorimetric indicators. The method allows locating the colorimetric sensor within the captured scene and to perform automated color correction to ensure color consistency regardless of the hardware used. To demonstrate it, a <semantics>CO2</semantics>-sensitive colorimetric indicator was printed on top of a paper-based substrate using screen printing. This indicator was formulated for Modified Atmosphere Packaging (MAP) applications. To verify the method, the sensors were exposed to several environmental conditions (both in gas composition and light conditions). And, images were captured with an 8M pixel digital camera sensor, similar to those used in smartphones. Our results show that the sensors have a relative error of 9% when exposed with a <semantics>CO2</semantics> concentration of 20%. This is a good result for low-cost disposable sensors that are not intended for permanent use. However, as soon as light conditions change (2500–6500 K), this error increases up to <semantics>ϵ20</semantics> = 440% (rel. error at 20% <semantics>CO2</semantics> concentration) rendering the sensors unusable. Within this work, we demonstrate that our color QR codes can reduce the relative error to <semantics>ϵ20</semantics> = 14%. Furthermore, we show that the most common color correction, white balance, is not sufficient to address the color consistency issue, resulting in a relative error of <semantics>ϵ20</semantics> = 90%.